Postharvest foliar nitrogen applications increase Neonectria ditissima leaf scar infection in apple trees - Dryden, G.H.; Nelson, M.A.; Smith, J.T.; Walter, M. (New Zealand Plant Protection, 2016)
Postharvest foliar nitrogen (urea) is often applied to apple leaves immediately after picking for bud fertilising and/or during leaf fall for Venturia inaequalis control During 20132016 ethylene diamine tetraacetic acid copper (EDTACu to enhance leaf abscission) urea calcium nitrate and BudWiser foliar treatments were applied alone or in combination to determine their effects on leaf scar infection by Neonectria ditissima in Braeburn (201314) Scifresh and Royal Gala (201516) orchards In 201314 leaf scar infection increased sixfold when 5 urea was added to EDTACu and sprayed at the onset of leaf fall In 201516 up to a ninefold increase in leaf scar infections was observed The timing of application was more important than the amount or form of nitrogen used As a result of this research the use of ureabased foliar nitrogen fertilisers for V inaequalis before leaf fall are not recommended and growers should consider all factors affecting Neonectria ditissima infections before applying nitrogen immediately after harvest